Depressive symptoms among elderly diabetic patients in Vietnam - Vu, Huyen Thi Thanh (Diabetes Metab Syndr Obes, 2018)
BACKGROUND AND AIMS: Depression and diabetes are becoming increasingly prevalent within the Vietnamese elderly population. However, the linkage between these health conditions in the Vietnamese elderly has not yet been fully investigated. This study aimed to assess the level of depressive symptoms and associated factors among elderly diabetic patients. METHODS: A cross-sectional study was conducted at National Geriatric Hospital in the elder patients aged ≥60 years with type 2 diabetes mellitus (T2DM). Depressive symptoms were assessed using the Geriatric Depression Scale, with three categories: normal (0–4 points), mild (5–9 points), and moderate/severe depressive symptoms (≥10 points). We obtained information on the patient’s sociodemographic, medical history, glycemic control (fasting plasma glucose and HbA(1c)), daily activities (activities of daily living [ADLs] and instruments activities of daily living [IADLs] scale), and fall risks (Time Up and Go test). Logistic regression was used to analyze the factors associated with the presence of depressive symptoms. RESULTS: Among 412 patients, 236 (57.3%) had HbA(1c) level at 7.0% or higher. There were 327 (79.4%) patients having depressive symptoms. The level of HbA(1c) was significantly different between the depressive symptom group and the non-depressive symptom group (7.74% and 6.61%, P<0.05). The increased likelihood of having depressive symptoms was associated with having risk of falls (OR: 5.50; 95% CI: 1.88–16.11), suffering from 5–10 years of diabetes (OR: 2.74, 95% CI: 1.28–5.85), uncontrolled fasting plasma glucose (OR: 4.06, 95% CI: 1.81–9.12), and an impairment of IADLs (OR: 5.74, 95% CI: 2.24–14.7). CONCLUSION: This study highlights a high prevalence of depressive symptoms among elderly T2DM patients in Vietnam, suggesting an urgent need for screening depressive symptoms and providing mental health care services to this population promptly, particularly to those suffering from diabetes for a long period of time or co-functional impairments.